Media Multitasking, Online Learning, and Social Media Activities among Adolescents - Suriati Gani (Graduate School of Universitas Negeri Malang, 2022)
Abstract: The increasing prevalence of the overuse of social media among adolescents has raised concerns. Educators worry that it may decrease the cognitive functioning of these adolescents. This study of 245 secondary-school students in Palu, Indonesia, reveals that there is a correlation between these students’ diminished perceived attention and the intensity of their internet and social media use. Due to their eagerness to multitask, students who check their social media notifications while doing their online learning experience perceived attention discontinuity. This study suggests the significance of prevention and intervention for adolescents’ media-related problems as they multitask in their online learning environments.